A Study on Erosion Wear Behavior of Alkaline and Silane Modified Coconut Sheath and Red Mud Reinforced Hybrid Composites. Issue 14 (28th October 2022) - Shanmugam, Vigneshwaran; Uthayakumar, M.; Arumugaprabu, V.; Abdul Majid, M.S.; Johnson, R. Deepak Joel
ABSTRACT: In the present work, the effect of erosion variable on the erosion rate of the novel coconut sheath fiber and red mud reinforced polyester composites is evaluated. The composites are fabricated with three forms of fiber reinforcement. Erosion experiment is conducted as per the ASTM G76 by varying impact angle, erodent velocity, and erodent discharge rate. The experiment design is modeled using the central composite design and analyzed using the response surface methodology and analysis of variance technique. The impact angle is found to be the most significant factor affecting the composite erosion rate. From erosion wear analysis, it is found that the interfacial adhesion between the fiber matrix is critical in the reduction of erosion rate. The composite with silane treated fiber showed reduced erosion rate when compared to the untreated and alkaline treated fiber composites. Further, the wear mechanism was analyzed on the eroded specimen using SEM analysis. Finally, the multiple response optimization was carried out using the desirability function method and found that erosion rate can be minimized at impact angle of 90°, erodent discharge rate of 4.45 g/m, and erodent velocity of 70 m/s.